«In questo picolo libretto» Descrizioni di feste e spettacoli per le nozze dei signori italiani del Rinascimento - PASSERA, CLAUDIO (Premio Ricerca «Città di Firenze», 2020)
In the second half of the XVth century, before the diplomatic balances that led to the birth of the regional states, the Italian rulers, in need of strategies to promote their public image, made their nuptials a powerful communication tool. Ceremonies, pageants and temporary architectures in honour of the newlyweds had the task of making explicit the alliances between the reigning houses of different principalities, visually expressing the power of the lords over their capitals. This book's aim is to understand how the festivities, orchestrated with court artists, became a means of celebratory propaganda and how the diffusion of their descriptions, in incunabula or manuscripts, heightened the fame of the events. The wedding feasts have been studied comparatively: comparing the variety of their theatrical performances, jousts and dances, as well as the ways of the production of the chronicles that handed down their memory, used here as sources for the history of the Renaissance spectacle.